Secondary Preventative Care for Patients After Spontaneous Coronary Artery Dissection: A Qualitative Analysis of Health Care Providers’ Perspectives - Bouchard, Karen; Tarannum, Chowdhury Nishwara; Coutinho, Thais; So, Derek; Tulloch, Heather (Canadian journal of cardiology, 2020)
Due to their unique demographic, cardiovascular, and psychologic profile, experts recommend that patients with spontaneous coronary artery dissection (SCAD) obtain tailored secondary preventative care. There is a need to glean perspectives from a diverse range of health care providers (eg, cardiology, general practice, and allied health) to supplement existing scientific statements and to delineate providers’ current approaches for delivering care. This study qualitatively investigated health care providers’ current practices, challenges, and recommendations for delivering secondary preventative care to patients with SCAD. Health care providers (n = 15) from a large cardiac health centre in Canada participated in individual semistructured interviews, which were analyzed with the use of inductive thematic coding techniques. Qualitative data revealed that participants recommend tailored cardiac rehabilitation, acknowledging the “uniqueness” of SCAD, offering provider-facilitated informational and peer support programming, increasing access to psychologic support throughout recovery, and enhancing health care provider education about SCAD. Limited psychologic resources, feasibility of sustaining programs with a small patient population, restrictive thresholds for physical activity, and reassuring patients amid scant evidence-based approaches were cited as major challenges to providing optimal care to patients after SCAD. In conclusion, participants suggest that tailored secondary prevention programming that acknowledges and targets the unique exercise, psychologic, and peer support needs of patients with SCAD, as well as increased education for health care providers, may be integral to promote patients in their recovery. En raison des profils démographiques, cardiovasculaires et psychologiques particuliers des patients qui subissent une dissection spontanée des artères coronaires (DSAC), les experts recommandent qu’ils obtiennent des soins de prévention secondaire individualisés. Il est nécessaire de recueillir les points de vue des divers fournisseurs de soins de santé (p. ex. en cardiologie, en pratique générale et en soins connexes) pour enrichir les énoncés scientifiques existants et décrire les approches actuelles des fournisseurs de soins. La présente étude a permis d’examiner sur le plan qualitatif les pratiques actuelles, les enjeux et les recommandations des fournisseurs de soins de santé sur la prestation des soins de prévention secondaire aux patients qui subissent une DSAC. Les fournisseurs de soins de santé (n = 15) d’un grand établissement de santé spécialisée en cardiologie du Canada ont participé à des entrevues individuelles semi-structurées analysées à l’aide de techniques de codification thématique selon une approche inductive. Les données qualitatives ont révélé que les participants recommandent d’offrir un programme de réadaptation cardiaque individualisé, qui reconnaît l’« unicité » de la DSAC, d’offrir un programme d’information et de soutien par les pairs animé par les fournisseurs, d’accroître l’accès au soutien psychologique pendant le rétablissement et d’améliorer la formation des fournisseurs de soins de santé sur la DSAC. Les ressources psychologiques limitées, le maintien des programmes qui regroupent une faible population de patients, les seuils restrictifs d’activité physique et la rassurance des patients devant le nombre insuffisant d’approches fondées sur des données probantes constituaient les principaux obstacles liés à la prestation de soins optimaux aux patients après la DSAC. En conclusion, les participants suggèrent qu’un programme de prévention secondaire individualisé, qui reconnaît et cible les besoins particuliers des patients ayant subi une DSAC en matière d’exercice, de soutien psychologique et de soutien par les pairs, et qu’une meilleure formation des fournisseurs de soins de santé sont essentiels pour encourager les patients dans leur rétablissement.